Lost Domain : Le Grand Meaulnes. - Alain-Fournier (Oxford University Press, 2013)
The arrival of Augustin Meaulnes at a small provincial secondary school sets in train a series of events that will have a profound effect on his life, and that of his new friend François Seurel. It is Seurel who recalls the impact of le grand Meaulnes, disruptive and charismatic, on his schoolmates, and the encounter that is to haunt them both. Lost, and alone, Meaulnes stumbles upon an isolated house, mysterious revels, and a beautiful girl. When hereturns to Seurel it is with the fixed determination to find the house again, and the girl with whom he has fallen in love. But the dreamlike days.